Translating through curating: Ivan Vladislavić’s portrait with keys and the creation of translating the keys - Appelbaum, Victoria (My University, 2020)
Interdisciplinarity in academia has become more prominent in recent years as the intersections of academic fields have become evident. This dissertation explores how a book can be translated through an exhibition, and what the implications of that translation are. Taking Portrait with Keys (2006) by Ivan Vladislavić, this project curatorially translates the book into exhibition form, then analysing the implications of the translation. The dissertation utilises the methodology of postcolonial translation theory to enact a curatorial translation of Portrait with Keys through participatory curation. In this way, the audience of the exhibition translated the book. The effectiveness of this translation is shown through the analysis of audience translations and the implications they have both for the book and curation, drawing out the ways in which the book was translated, proving how curation can be used to produce an afterlife of a text. In undertaking this research, the scholarly writing around exhibitions and exhibition praxis in South Africa is developed, furthering the study of curating and participatory exhibitions as a mode of research. This dissertation delves into a variety of fields, bringing together translation studies, curatorial studies, literary studies, and urban studies. By developing interdisciplinary links, this dissertation illustrates the possibilities for researching across disciplines in order to further all fields involved
A dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Arts by Dissertation (History of Art), 2020